Microservices‐based databank for Turkish hazelnut cultivars using IoT and semantic web technologies - Aydin, Sahin; Aldara, Dieaa (Wiley, 2024)
SummaryInformation and communication technologies (ICTs) can play a crucial role in facilitating access to comprehensive information on the quality standards of Turkish hazelnut cultivars. In this regard, this study introduces a Hazelnut Databank System (HDS) that utilizes the microservices architecture, an integrated software system supported by the Internet of Things (IoT) and semantic web, to categorize Turkish hazelnut cultivars. The study focuses on developing microservices using various programming languages and frameworks. Specifically, C# on the .NET Core Framework was used for both microservices and the web‐based application implemented through the ASP.NET Core MVC Framework. Mobile‐based software applications were created using Xamarin. Forms, and the IoT application was developed using the Python programming language. The data storage is facilitated through the MS SQL Server database. Additionally, the study incorporates the implementation of a hazelnut species classification system using the DNN + ResNet50 machine learning model, achieving an impressive accuracy rate of 95.77%. The overall usability of the system was evaluated, resulting in a score of 42 out of 50. By providing detailed information on Turkish hazelnut cultivars, the HDS has the potential to greatly improve hazelnut production quality in Turkey and increase awareness of hazelnut agriculture among relevant stakeholders.
Keywords: Application programs; Internet of things; Classification (of information); Digital storage; Information dissemination; Agriculture; Agricultural informations; Agricultural information dissemination; Hazelnut databank system; Hazelnut shape categorization; Turkishs; Microservices in agriculture; Turkish hazelnut cultivars; Databanks; Semantic Web technology; Hazelnut classification; Semantic Web